Linear dynamics subject to thermal fluctuations and non-Gaussian noise: from classical to quantum - M Köpke; J Ankerhold (New Journal of Physics, 2013)
The dynamics of a linear system embedded in a heat bath environment and subject to white non-Gaussian noise is studied. Classical higher-order cumulants in coordinate space are derived for Poissonian noise and their impact on the dynamics and on asymptotic steady-state distributions is analyzed. In the quantum regime, non-Gaussian properties are present in reduced density in coordinate representation, but in energy representation they exist on a transient time scale only, due to symmetry. Within an exactly solvable model, our results provide insight into mechanisms of linear detectors as sensors for non-Gaussian noise at high and low temperatures.